Neonatal handling decreases unconditioned anxiety, conditioned fear, and improves two-way avoidance acquisition: a study with the inbred Roman high (RHA-I)- and low-avoidance (RLA-I) rats of both sexes - Río-Alamos, Cristobal; Puigdellivol, Ignasi O.; Cañete, Antoni; Blazquez, Gloria; Martinez-Membrives, Esther; Tobeña, Adolf; Fernandez-Teruel, Alberto (Frontiers in Behavioral Neuroscience, 2015)
The present study evaluated the long-lasting effects of neonatal handling (H; administered during the first 21 days of life) on unlearned and learned anxiety-related responses in inbred Roman High- (RHA-I) and Low-avoidance (RLA-I) rats. To this aim, untreated and neonatally-handled RHA-I and RLA-I rats of both sexes were tested in the following tests/tasks in “baseline acoustic startle” (BAS) test, a “context-conditioned fear” (CCF) test and the acquisition of two-way active –shuttle box- avoidance (SHAV). RLA-I rats showed higher unconditioned (NOE, ZM, BAS) and conditioned (CCF, SHAV) anxiety. H treatment increased exploration of the novel object in the NOE test as well as exploration of the open sections of the ZM test in both rat strains and sexes, although the effects were relatively more marked in the (high anxious) RLA-I strain and in females. Neonatal handling did not affect BAS, but reduced context-conditioned fear in both strains and sexes, and improved shuttle box avoidance acquisition especially in RLA-I (and particularly in females) and in female RHA-I rats. These are completely novel findings, and may suggest that H-induced changes in hippocampal function, which is enhanced in RLA-Is vs RHA-I rats, could be a candidate mechanism underlying the observed long-lasting benefits of neonatal handling on known hippocampal-dependent responses/tasks.